2016
DOI: 10.5812/ijp.8151
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Skin-to-Skin Care and its Effect on Cortisol Levels of the Infants

Abstract: Background: Neonatal period is one of the most important critical phases of human life. Intensive care unit has a stressful environment for the infant in which the patient will be under the pressure of factors such as noise, nursing intervention and harsh light; the most important factor in this regard being separation from parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…Indeed, Morelius et al [ 54 ] found that mothers suffered a significant decrease in cortisol levels during their first SSC or after the SSC was over but not during the intervention. This outcome was confirmed by the study of Mirnia et al [ 52 ], where in both skin-to-skin groups and standard ward treatment groups, cortisol in neonates decreased. In particular, compared with similar time intervals in the group with usual care, the cortisol level in neonates during SSC decreased more.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Indeed, Morelius et al [ 54 ] found that mothers suffered a significant decrease in cortisol levels during their first SSC or after the SSC was over but not during the intervention. This outcome was confirmed by the study of Mirnia et al [ 52 ], where in both skin-to-skin groups and standard ward treatment groups, cortisol in neonates decreased. In particular, compared with similar time intervals in the group with usual care, the cortisol level in neonates during SSC decreased more.…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, analysis of the 22 selected studies revealed that nine studies focused on HRV [ 36 , 38 , 44 , 45 , 46 , 47 , 48 , 50 , 51 ], six studies on stress [ 26 , 36 , 38 , 41 , 54 , 55 ], and nine on cortisol [ 40 , 42 , 43 , 51 , 52 , 54 , 55 , 56 , 57 ], while the remaining six focused on oxytocin [ 40 , 43 , 48 , 53 , 55 , 57 ]. The studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 14 studies, five were defined by the authors as randomised controlled trials, 22 , 23 , 24 , 25 , 26 seven were crossover trials, 27 , 28 , 29 , 30 , 31 , 32 , 33 one was quasi‐experimental 13 and one had a retrospective design. 34 The main characteristics of the study designs are summarised in Table 2 .…”
Section: Resultsmentioning
confidence: 99%